1999
DOI: 10.1211/0022357991772312
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychopharmacological Profile of the Methanolic Fraction of Bryophyllum pinnatum Leaf Extract

Abstract: Neuropharmacological studies were conducted in experimental animals (rats and mice) with the methanolic fraction of Bryophyllum pinnatum leaf extract. The fraction produced alteration of behaviour pattern, caused dose-dependent potentiation of pentobarbitone sleeping time and had significant analgesic activity. Significant reduction of exploratory behaviour and loss of residual curiosity were among the effects observed with the fraction. The observations suggest that the methanolic fraction of Bryophyllum pinn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
2
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(70 citation statements)
references
References 10 publications
4
63
2
1
Order By: Relevance
“…13,14 In our study HEPBL showed to inhibit the pain by both the central as well as peripheral mechanism. Hence we assume that the analgesic action of HEPBL could have been mediated through narcotic mechanism.…”
Section: Discussionsupporting
confidence: 48%
“…13,14 In our study HEPBL showed to inhibit the pain by both the central as well as peripheral mechanism. Hence we assume that the analgesic action of HEPBL could have been mediated through narcotic mechanism.…”
Section: Discussionsupporting
confidence: 48%
“…Using the chemical method described above, the aqueous extract and stigmast-4,20(21),23-trien-3-one (47) significantly reduced the number of contractions by 80.16 % and 75.72 %, respectively. The methanolic fraction also showed a significant reduction of contractions [40,80]. At doses of 100-300 mg/kg b. w., the aqueous leaf extract increased the pain threshold in rats in the hot plate assay, and reduced phenylbenzoquinone-induced writhing in mice [97].…”
Section: Antiulcer Activitymentioning
confidence: 90%
“…Some of these neuropharmacological effects were tested in Swiss mice applying a methanolic fraction. The GABA content in the brain was estimated after i. p. administration, and the methanolic fraction led to an increase in brain GABA concentration [80]. The compounds responsible for the neurological activity are not definitively known, but a neurosedative effect of bersaldegenin-1,3,5-orthoacetate (3) was demonstrated in mice, whereby strongly sedative activity was observed with doses of 0.1-0.5 mg/kg b. w. However, higher doses resulted in paralysis and muscle contractions [23].…”
Section: Sleep and Neurological Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…The tail flick test measures complex responses to acute nociceptive activity and is one of the models used for studying centrally acting analgesics [14]. The extract showed a potent activity on this model, similar to the effect of morphine.…”
Section: Discussionmentioning
confidence: 97%